Comparative analysis of frameworks used in automated testing on example of TestNG and WebdriverIO - Shtokal, Alla; Smołka, Jakub (Journal of Computer Sciences Institute, 2021)
The article presents a comparative analysis of frameworks supporting the development of automated tests for defined test scenarios. The comparative study concerned the TestNG and WebDriverIO frameworks. The overview of the tool has been analyzed both in terms of the test development process as well as the speed and efficiency of their execution. The website github.com was used for the purposes of the work. This application was used to run test scripts written in both frameworks. The results were compared by five defined criteria: the time of running the test files in different browser operation modes, the average value of memory and CPU usage during the test execution. The summary includes the evaluation of the compared frameworks.